Pojęcie osób pozostających we wspólnym pożyciu – analiza dogmatyczna - Matynia, Justyna (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The article is bringing up the issue of interpretative doubts associated with re-asserting the group of persons closest on land Art. 115 § 11 of the Polish penal code. The author is pointing at a number of problems which can directly be connected with notre-asserting by the legislator the discussed notion. The text contains the inspection of the hypothetical actual states of affairs, on the canvas of which the address closest to the problem of proper categorising persons acting in it as persons is probable, be as persons staying with the perpetrator in particularly a personal close rapport. The article is polemicizing with stating the part of representatives of the criminal law, that with crucial element enabling for categorising persons as staying in the cohabitation there is an existence of the economic bond. The author claims that the most important is emotional bond between two people.